2019
DOI: 10.29101/crcs.v26i80.11248
|View full text |Cite
|
Sign up to set email alerts
|

La brecha salarial de género en las instituciones científicas. Estudio de caso

Abstract: El estudio al que se refiere este artículo pretende identificar factores internos y externos que son constitutivos de la brecha salarial de género en una institución científica, concretamente en la Universidad de Valencia, que se analizan a partir de los datos del registro de nóminas de 2015. Se ha examinado la brecha salarial ajustada por hora trabajada, la brecha doblemente ajustada (por hora y categoría) y triplemente ajustada (por hora, categoría y complemento retributivo). La brecha salarial de género se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 12 publications
0
6
0
22
Order By: Relevance
“…In line with this perspective, a large number of existing studies have examined the persistence of gender imbalance in the scientific structure [1,[4][5][6]. It has been suggested that women have a lower wage [7,8], are promoted more slowly [9], receive less research funding [10], and their proportion in editorial and faculties boards is lower [2] A different line of studies of gender imbalance has focused on knowledge production. There is a wide choice of literature discussing the persistence of gender differences in the production and publication of scientific knowledge, such as bias in the journal reviewing process [11], differences in the number of citations of their work in comparison with their male colleagues [11], a gender asymmetry in collaborations [12] or even, a disparity in commenting on published academic research [13].…”
mentioning
confidence: 99%
“…In line with this perspective, a large number of existing studies have examined the persistence of gender imbalance in the scientific structure [1,[4][5][6]. It has been suggested that women have a lower wage [7,8], are promoted more slowly [9], receive less research funding [10], and their proportion in editorial and faculties boards is lower [2] A different line of studies of gender imbalance has focused on knowledge production. There is a wide choice of literature discussing the persistence of gender differences in the production and publication of scientific knowledge, such as bias in the journal reviewing process [11], differences in the number of citations of their work in comparison with their male colleagues [11], a gender asymmetry in collaborations [12] or even, a disparity in commenting on published academic research [13].…”
mentioning
confidence: 99%
“…Universidad de Valencia, 2015. Brecha Salarial de Género según rangos de edad y tenencia de hijas/os Fuente: Jabbaz, Samper y Díaz, 2019. análisis de sexo/género y transformando el conocimiento, de forma acorde con ese análisis. No hay más que ver las propuestas de la Comisión Europea para potenciar la investigación con perspectiva de género, fundamentalmente en el Programa Marco que está fi nalizando (Horizonte 2020) 8 y en el próximo que ya está casi totalmente elaborado (Horizonte Europa) 9 .…”
Section: Los Contenidos Androcéntricos De La Ciencia Y De La Docenciaunclassified
“…Fuente : Jabbaz, Samper y Díaz, 2019. categoría y horas trabajadas (brecha salarial doblemente ajustada), en la Universidad de Valencia la brecha es de 1,3% entre ayudantes doctores, de 3,99% entre titulares de universidad y de 2,44% en el caso de las cátedras. Si no ajustamos por categoría y horas trabajadas (brecha bruta) la brecha alcanza el 10,9% para toda la universidad, incluido el PAS, que tiene una brecha bruta menor que el PDI.…”
Section: La Brecha Salarial De Génerounclassified
See 2 more Smart Citations